2017
DOI: 10.1073/pnas.1703422114
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-induced conformational dynamics of the Escherichia coli Na + /H + antiporter NhaA revealed by hydrogen/deuterium exchange mass spectrometry

Abstract: Na/H antiporters comprise a family of membrane proteins evolutionarily conserved in all kingdoms of life and play an essential role in cellular ion homeostasis. The NhaA crystal structure of has become the paradigm for this class of secondary active transporters. However, structural data are only available at low pH, where NhaA is inactive. Here, we adapted hydrogen/deuterium-exchange mass spectrometry (HDX-MS) to analyze conformational changes in NhaA upon Li binding at physiological pH. Our analysis revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 60 publications
3
43
0
Order By: Relevance
“…8, D and E). Surface residues on both PDZ domains displayed higher deuteration on a short time scale, consistent with the view that solvent accessibility in the crystal structure correlates with the relative deuterium uptake (63). Strikingly, the ␤-sheets in PDZ2 (Fig.…”
Section: Structural Determinants Of Nherf1 Binding To Npt2a and Confosupporting
confidence: 83%
“…8, D and E). Surface residues on both PDZ domains displayed higher deuteration on a short time scale, consistent with the view that solvent accessibility in the crystal structure correlates with the relative deuterium uptake (63). Strikingly, the ␤-sheets in PDZ2 (Fig.…”
Section: Structural Determinants Of Nherf1 Binding To Npt2a and Confosupporting
confidence: 83%
“…The main structural model used to study Nha orthologs is Escherichia coli NhaA, for which a crystallographic structure of the inactive state at acidic pH is available (Hunte et al, 2005). To study the structural dynamics of NhaA under physiological pH, HDX-MS was recently used (Eisinger et al, 2017). Crucial to the insights obtained in this study, HDX-MS provides global dynamic data, in contrast to methods based on site-specific labeling, which only detect movements of pre-defined protein regions.…”
Section: Conformational Transitions Underlyingmentioning
confidence: 99%
“…For example, the hydrophobic transmembrane segments of MPs can be inherently difficult to digest and observe by LC-MS, although this is often protein and digestion condition dependent [189], and does not always preclude structural analyses. Recent studies on detergent and lipid solubilized proteins have demonstrated that both are compatible with HDX-MS [181,[190][191][192][193][194][195].…”
Section: Hydrogen/deuterium Exchangementioning
confidence: 99%
“…8) [190]. The conformational changes in green cone opsin upon light activation have also been studied [196], as well as the alternating access mechanism of the Na + /H + antiporter NhaA [191].…”
Section: Hydrogen/deuterium Exchangementioning
confidence: 99%